Didactic tendencies of some university mathematics teachers (2020)
The article presents an analysis of the teaching work of teachers of the Degree in Mathematics of the Pedagogical and Technological University of Colombia, which can be considered as a starting point to improve classroom practices. The theoretical approach is that of class models proposed by Porlán, complemented by Piaget’s classical constructivism, Vygotsky’s socio-cultural approach, and Bruner’s interactionism. The research methodologyis mixed, with a descriptive scope. The instruments used to collect information were questionnaires and unstructured interviews. The results show that most of the teachers who participated in the research: design their classes based on operational objectives; assess through the application of objective tests, posed especially as guides; and consider that learning occurs through a progressive process of concept assimilation. According to the aforementioned, it is evident that the characteristics of teachers’ practices are associated with a technological didactic tendency.